Business Performance in Automotive Vehicle Customs Business in Indonesia - Herma Rio Candra Saputra; Adi Santoso; Dwi Warni Wahyu (Journal of Entrepreneurship and Business, 2023)
Purpose: This study aims to determine Business Performance in Automotive Vehicle Customs Business in Indonesia. This study uses the RBV basis in analyzing phenomena and research findings. The population of this study is the owners of customs workshops throughout Indonesia. Method:The number of samples is determined using the Isaac table equation to obtain a total sample of 300 respondents. Data collection uses questionnaires that are distributed offline and online. Data measurement uses answers Strongly Agree, Agree, Disagree, Strongly Disagree, with a rating scale of 1 to 4. Data processing uses the SMART PLS3 application. The results of this study found that Customer Orientation, Adaptive Technology, and Marketing Capability had a positive effect on the Business Performance of custom workshops. This can be seen from the results of the discriminate validity test and the final result of Smart PLS3 data processing. Result: This study found that Customer Orientation, Adaptive Technology, and Marketing Capability positively affected the Business Performance of custom workshops. This can be seen from the results of the discriminate validity test and the final result of Smart PLS3 data processing. The findings of this study support the study that Customer Orientation towards repair shop customers, Adaptive Technology of workshops in the production of custom motorbikes, and Marketing Capability owned by custom repair shops have a good effect in the long term. This is strengthened because the custom workshop is a service industry that prioritizes the needs and desires of its customers; they work and produce based on online and offline market demands apart from the needs of company assets. The public and their customers will notice the use and application of technology in completing custom motorbikes. This is the opinion given by the custom builders that I met. They explained that in the production of custom motorcycles, we must meet the needs and wishes of customers, which will affect market demand for custom motorcycle orders that we will work on later. These results support the finding that research on custom builders will increase if we can meet the needs and desires of consumers and markets on a widespread or commercial basis.